NUTRIENT FULFILLMENT OF MOTHERS DURING PUERPURIUM PERIOD IN THE SE’I CULTURE AT SUBDISTRICT OF MOLO SELATAN DISTRICT OF TIMOR TENGAH SELATAN - ALBERTH MATUSALAK BAU MALI; I MADE ALIT GUNAWAN; SUMARNI SUMARNI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Background: Se’I culture is a series of activities aimed to take care of mother during puerperium that consisted of abstain from certain foods, warming of mothers and Tatobi (compress) within 40 days. Mother during lactation period belong to age group that are susceptible to lack of nutrition because while breastfeeding the baby, they are undergoing recovery, menstruation and fulfilling their physical needs. Besides, during breastfeeding mother loose micro and macro nutrients such as zinc and calcium exerted throug breast milk. Abstain from food, either in types, amount or frequency, will bring negative impact to the fulfillment of mother during parturition period.Objective: the study aimed to get an overview of the nutrient fulfillment of mother during puerperium in relation to the implementation of Se’I culture among Timor tribe.Method: the study was qualitative that used phenomenological approach with mother during puerperium period of Timor tribe as subject of the study. Data were obtained through indepth interview, observation and food recall 24 hours. Data analysis used Miles and Huberman Model. Result: care that was carried out during the implementation of Se’I culture aimed to support the process of recovery and maintain the physical condition as it was before pregnancy. The fulfillment of nutrients of mother during the practice of Se’I did not meet nutrition sufficiency as recommended.Conclution: intake of nutrition of mothers during the practice of Se’I did not fulfill the need for nutrition and consume other foods that contained equal amount of nutrients when mothers were abstain from certain types of foods.